Exploring Indonesian Lecturers' Perceptions and Practices on English Language Assessment - Imam Munandar; Shaumiwaty Shaumiwaty (Vision: Journal for Language and Foreign Language Learning, 2023)
Assessments are crucial in teaching English as a Foreign Language (EFL), impacting students' knowledge acquisition and influencing teachers' beliefs and training. The present research investigates lecturers' fundamental conceptions regarding assessing English as a foreign language (EFL) and their instructional practices in higher education. Twelve English department EFL lecturers participated in a study using purposive sampling, semi-structured interviews, and questionnaires. The research used a thematic analysis methodology to identify themes, classifications, and subcategories reflecting respondents' perspectives on EFL evaluation. The study's results showed that the subjects used diverse terminology to illustrate evaluation, offering a stimulating context for their respective methodologies. Furthermore, the participants believed that language assessment serves multiple purposes, including administrative and educational functions. Most respondents viewed evaluation as a continuation of English as a Foreign Language (EFL) classroom instruction and acquisition, significantly influencing students' educational outcomes and learning strategies. Therefore, considering how assessments can improve student learning will likely influence educators' working in EFL assessment. Research highlights the need for professional development for lecturers to improve their understanding of language assessment and practice through workshops, training sessions, and resources.